Hubungan Diplomatik antara Indonesia dan Taiwan dalam konteks Kebijakan Arah Selatan Baru Taiwan - Tri Nguyen Minh; Nguyen Le Tam (Public Knowledge, 2026)
This study analyzes the bilateral relations between Indonesia and Taiwan within the framework of the New Southbound Policy (NSP) launched by the Tsai Ing-wen administration in 2016. Using a qualitative descriptive-analytical approach and a multidisciplinary theoretical framework combining strategic realism and soft power theory, this research examines how both entities navigate complex interdependence despite the absence of formal diplomatic ties. The findings indicate that Indonesia occupies a crucial position in the NSP due to its strategic maritime geography and “Free and Active” foreign policy, which allows for substantial pragmatic cooperation in non-political sectors. Economic data reveal a solid growth trend, with bilateral trade exceeding $14 billion in 2022 and significant Taiwanese FDI in Indonesia's strategic industries. Furthermore, the study identifies a “soft power gap” in educational exchanges and highlights the vital role of the Indonesian migrant worker community and halal tourism as grassroots bridges that strengthen socio-cultural ties. The research concludes that the sustainability of this partnership relies on leveraging these non-political channels to align with Indonesia's national priorities, such as the Golden Indonesia Vision 2045, while managing regional strategic competition.